Manufacturing of Microfluidic Devices with Interchangeable Commercial Fiber Optic Sensors - Krystian L. Wlodarczyk (MDPI AG, 2021)
In situ measurements are highly desirable in many microfluidic applications because they enable real-time, local monitoring of physical and chemical parameters, providing valuable insight into microscopic events and processes that occur in microfluidic devices. Unfortunately, the manufacturing of microfluidic devices with integrated sensors can be time-consuming, expensive, and “know-how” demanding. In this article, we describe an easy-to-implement method developed to integrate various “off-the-shelf” fiber optic sensors within microfluidic devices. To demonstrate this, we used commercial pH and pressure sensors (“pH SensorPlugs” and “FOP-MIV”, respectively), which were “reversibly” attached to a glass microfluidic device using custom 3D-printed connectors. The microfluidic device, which serves here as a demonstrator, incorporates a uniform porous structure and was manufactured using a picosecond pulsed laser. The sensors were attached to the inlet and outlet channels of the microfluidic pattern to perform simple experiments, the aim of which was to evaluate the performance of both the connectors and the sensors in a practical microfluidic environment. The bespoke connectors ensured robust and watertight connection, allowing the sensors to be safely disconnected if necessary, without damaging the microfluidic device. The pH SensorPlugs were tested with a pH 7.01 buffer solution. They measured the correct pH values with an accuracy of ±0.05 pH once sufficient contact between the injected fluid and the measuring element (optode) was established. In turn, the FOP-MIV sensors were used to measure local pressure in the inlet and outlet channels during injection and the steady flow of deionized water at different rates. These sensors were calibrated up to 140 mbar and provided pressure measurements with an uncertainty that was less than ±1.5 mbar. Readouts at a rate of 4 Hz allowed us to observe dynamic pressure changes in the device during the displacement of air by water. In the case of steady flow of water, the pressure difference between the two measuring points increased linearly with increasing flow rate, complying with Darcy’s law for incompressible fluids. These data can be used to determine the permeability of the porous structure within the device.